Solid polymer electrolyte membrane, membrane-electrode assembly, water electrolysis device, hydrogen production method, and method for manufacturing membrane-electrode assembly

By using a solid polymer electrolyte membrane containing fluoropolymers, platinum, and cerium oxide particles in a water electrolysis device, the problems of voltage rise and pinhole formation were solved, achieving a stable and efficient water electrolysis process.

CN122122339APending Publication Date: 2026-05-29AGC INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480068577.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-27
Filing Date
2024-12-26
Publication Date
2026-05-29

AI Technical Summary

Technical Problem

Existing solid polymer water electrolysis devices are prone to problems such as increased electrolysis voltage and pinhole formation after a certain period of water electrolysis.

Method used

A solid polymer electrolyte membrane containing fluoropolymers, platinum-containing materials, and cerium oxide particle aggregates is used. By controlling the average particle size of the aggregates and the distribution of platinum-containing materials, the ion exchange capacity and the configuration of the catalyst layer are optimized to form a multilayer or single-layer membrane electrode assembly.

Benefits of technology

It effectively suppressed the rise in electrolysis voltage after water electrolysis for a certain period of time, reduced the generation of pinholes, and improved the stability and efficiency of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122122339A_ABST
    Figure CN122122339A_ABST
Patent Text Reader

Abstract

Provided is a solid polymer electrolyte membrane that can suppress an increase in electrolysis voltage after water electrolysis for a certain period of time and is less likely to generate pinholes. A solid polymer electrolyte membrane includes a fluorine-containing polymer having an ion exchange group, a platinum-containing substance, an aggregate of cerium oxide particles, and a woven fabric, the aggregate having an average particle diameter of 0.1 to 10 μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to solid polymer electrolyte membranes, membrane electrode assemblies, water electrolysis devices, methods for manufacturing hydrogen, and methods for manufacturing membrane electrode assemblies. Background Technology

[0002] The application of solid polymer water electrolysis devices (PEM type water electrolysis devices) is being studied, focusing on the conversion of surplus electricity into gas for storage and utilization.

[0003] For example, Patent Document 1 discloses a solid polymer water electrolysis device having a membrane electrode assembly comprising: an anode and a cathode having a catalyst layer; and a solid polymer electrolyte membrane disposed between the anode and the cathode.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: International Publication No. 2022 / 050363 Summary of the Invention

[0007] The problem the invention aims to solve

[0008] In recent years, there has been a demand for further improvements in the performance of water electrolysis devices.

[0009] The inventors evaluated the water electrolysis device with a solid polymer electrolyte membrane described in Patent Document 1 and found that it was sometimes difficult to suppress the rise in electrolysis voltage and the formation of pinholes after a certain period of water electrolysis.

[0010] This disclosure was made in view of the above-mentioned problems. One embodiment of the present invention aims to provide a solid polymer electrolyte membrane, a membrane electrode assembly, a water electrolysis apparatus, a method for producing hydrogen, and a method for producing a membrane electrode assembly that can suppress the rise of electrolysis voltage after water electrolysis for a certain period of time and are not prone to pinholes.

[0011] Solution for solving the problem

[0012] The present invention has the following aspects. [1]

[0014] A solid polymeric electrolyte membrane comprises: a fluoropolymer having ion-exchange groups, a platinum-containing compound, an aggregate containing cerium oxide particles, and a fabric.

[0015] The average particle size of the aggregates is 0.1–10 μm. [2]

[0017] According to the solid polymer electrolyte membrane described in [1], the average particle size of the aggregates is greater than 3 μm. [3]

[0019] According to the solid polymer electrolyte membrane described in [1] or [2], the ion exchange capacity of the fluorinated polymer is 0.90~2.00 milliequivalents / gram of dry resin. [4]

[0021] According to any one of [1] to [3], the solid polymer electrolyte membrane, wherein per 1 cm 2 The mass of the aggregate in the aforementioned solid polymer electrolyte membrane is 0.010 mg / cm³. 2 above. [5]

[0023] The solid polymer electrolyte membrane according to any one of [1] to [4], wherein the platinum-containing material is predominantly present on one surface side of the solid polymer electrolyte membrane. [6]

[0025] The solid polymer electrolyte membrane according to any one of [1] to [5], wherein the platinum-containing material is loaded on a carrier. [7]

[0027] The solid polymer electrolyte membrane according to any one of [1] to [6], wherein the ion exchange group of the fluorinated polymer is a sulfonic acid type functional group. [8]

[0029] The solid polymer electrolyte membrane according to any one of [1] to [7], wherein the fluoropolymer comprises the unit shown in formula (1-1) described later.

[0030]

[0031] In equation (1-1), R f1 M is a perfluoroalkylene group that optionally contains oxygen atoms between carbon atoms, and M is a hydrogen atom, an alkali metal, or a quaternary ammonium cation. [9]

[0033] The solid polymer electrolyte membrane according to any one of [1] to [8], wherein the fabric is composed of a material selected from the group consisting of polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polyether ether ketone and polyphenylene sulfide.

[10]

[0035] A membrane electrode assembly comprising:

[0036] The solid polymer electrolyte membrane described in any one of [1] to [9],

[0037] The cathode catalyst layer disposed on one side of the aforementioned solid polymer electrolyte membrane, and

[0038] An anode catalyst layer is disposed on the other side of the aforementioned solid polymer electrolyte membrane.

[11]

[0040] A water electrolysis device, comprising:

[0041]

[10] The membrane electrode assembly described above;

[0042] The power supply unit is connected to the cathode catalyst layer side and the anode catalyst layer side of the aforementioned membrane electrode assembly; and

[0043] The water supply unit supplies water to the anode catalyst layer.

[12]

[0045] A method for producing hydrogen, wherein hydrogen is produced by electrolyzing water using the water electrolysis device described in

[11] .

[13]

[0047] A method for manufacturing a membrane electrode assembly, the membrane electrode assembly comprising:

[0048] The solid polymer electrolyte membrane, cathode catalyst layer and anode catalyst layer as described in any one of [1] to [9],

[0049] In the manufacturing method, the cathode catalyst layer is formed on one side of the solid polymer electrolyte membrane, and the anode catalyst layer is formed on the other side of the solid polymer electrolyte membrane.

[0050] The effects of the invention

[0051] According to one embodiment of the present invention, a solid polymer electrolyte membrane, a membrane electrode assembly, a water electrolysis device, a method for producing hydrogen, and a method for producing the membrane electrode assembly can be provided, which are capable of suppressing the rise of electrolysis voltage after water electrolysis for a certain period of time and are not prone to pinholes. Attached Figure Description

[0052] Figure 1 This is a cross-sectional schematic diagram of a solid polymer electrolyte membrane used to illustrate the state in which platinum-containing substances are present in a predominantly heavy state.

[0053] Figure 2 This is a cross-sectional view schematically illustrating an example of a membrane electrode assembly of the present disclosure.

[0054] Figure 3 This is a cross-sectional view schematically illustrating an example of a membrane electrode assembly of the present disclosure. Detailed Implementation

[0055] Unless otherwise specified, the definitions of the following terms apply to the entire scope of this specification and the claims.

[0056] "Ion exchange group" refers to a group that can exchange at least a portion of the ions contained in the group for other ions. Examples include sulfonic acid functional groups and carboxylic acid functional groups.

[0057] "Sulfonic acid functional group" refers to a sulfonic acid group (-SO3H) or a sulfonate group. Examples of sulfonate groups include (-SO3H). - Ma + 、(-SO3 - 2Mb 2+ and (-SO3) - 3Mc 3+ (where Ma) + Mb is an alkali metal ion or a quaternary ammonium cation. 2+ Mc is a divalent metal ion. 3+ (It is a trivalent metal ion.) It should be noted that when there are 2 ligands, the number of ion exchange groups is 2, and when there are 3 ligands, the number of ion exchange groups is 3.

[0058] "Carboxylic acid type functional group" refers to a carboxylic acid group (-COOH) or a carboxylate group. Here, examples of carboxylate groups include (-COO)... - Ma + 、(-COO - 2Mb 2+ and (-COO) - 3Mc 3+ (where Ma) + Mb is an alkali metal ion or a quaternary ammonium cation. 2+ Mc is a divalent metal ion. 3+ (It is a trivalent metal ion.) It should be noted that when there are 2 ligands, the number of ion exchange groups is 2, and when there are 3 ligands, the number of ion exchange groups is 3.

[0059] "Precursor membrane" refers to a membrane containing polymers with groups that can be converted into ion exchange groups.

[0060] "A group that can be converted into an ion exchange group" refers to a group that can be converted into an ion exchange group through treatments such as hydrolysis or acidification.

[0061] "A group that can be converted into a sulfonic acid functional group" refers to a group that can be converted into a sulfonic acid functional group through treatments such as hydrolysis or acidification.

[0062] "A group that can be converted into a carboxylic acid functional group" refers to a group that can be converted into a carboxylic acid functional group through known treatments such as hydrolysis or acidification.

[0063] In polymers, a "unit" refers to a group of atoms based on one molecule of that monomer, formed through the polymerization of the monomer. A unit can be a group of atoms formed directly through the polymerization reaction, or it can be a group of atoms whose structure is transformed by processing the polymer obtained through the polymerization reaction.

[0064] The numerical range indicated by "~" refers to the range including the values ​​recorded before and after "~" as both lower and upper limits. Within the numerical ranges described in stages in this specification, the upper or lower limit recorded in a particular numerical range can be replaced by the upper or lower limit of a numerical range described in other stages. Furthermore, within the numerical ranges described in this specification, the upper or lower limit recorded in a particular numerical range can also be replaced by the values ​​shown in the embodiments.

[0065] [Electrolyte membrane]

[0066] The solid polymer electrolyte membrane disclosed herein (hereinafter also referred to as "electrolyte membrane") comprises: a fluoropolymer having ion exchange groups (hereinafter also referred to as "fluoropolymer (I)"), a platinum-containing compound, an aggregate containing cerium oxide particles, and a fabric.

[0067] The average particle size of the above aggregates is 0.1~10μm.

[0068] Hereinafter, the aggregate containing cerium oxide particles with an average particle size of 0.1 to 10 μm in this invention will also be referred to as "this aggregate".

[0069] The inventors have discovered that in electrolyte membranes containing aggregates of cerium oxide particles with an average particle size of less than 0.1 μm, the electrolysis voltage tends to increase after a certain period of water electrolysis when applied to a water electrolysis device. Because the cerium oxide particles are small, their surface area increases. If water electrolysis is performed for a certain period (e.g., 500 hours) using such relatively small cerium oxide particles, cerium easily dissolves from the cerium oxide particles over time. It is speculated that this dissolved cerium leads to a decrease in the proton conductivity of the ionomers in the electrolyte membrane and catalyst layer, resulting in a tendency for the electrolysis voltage to increase.

[0070] Furthermore, it was found that in electrolyte membranes containing aggregates of cerium oxide particles with an average particle size greater than 10 μm, the mesh size of the fabric tends to expand during operation of the water electrolysis device. This expansion causes swelling and thus easily leads to pinholes. In such cases, it is hypothesized that using this aggregate (an aggregate containing cerium oxide particles with an average particle size of less than 10 μm) could suppress the expansion of the fabric mesh and thus reduce the likelihood of pinholes.

[0071] Electrolyte membranes can be single-layer or multi-layer structures. Specific examples of multi-layer electrolyte membranes include: stacking multiple electrolyte layers with different contents of at least one of the platinum-containing substance and the aggregate; and stacking multiple electrolyte layers with different ion exchange capacities.

[0072] When the electrolyte membrane contains both a platinum-containing compound and the aggregate in the same layer, it is preferred because the cerium oxide contained in the aggregate can effectively recover hydroxyl radicals from hydrogen peroxide generated when the platinum-containing compound recombines hydrogen and oxygen.

[0073] The platinum-containing compounds and this aggregate contained in the electrolyte membrane can be dispersed throughout the electrolyte membrane or they can be concentrated on one surface side of the electrolyte membrane.

[0074] When the material is predominantly present on one surface side of the electrolyte membrane, it is preferable that at least one of the platinum-containing compound and the aggregate is predominantly present on one surface side of the electrolyte membrane, and more preferably, at least one of the platinum-containing compound and the aggregate is predominantly present on one surface side of the electrolyte membrane. Alternatively, both the platinum-containing compound and the aggregate (i.e., both the platinum-containing compound and the aggregate) may be predominantly present on one surface side of the electrolyte membrane.

[0075] When applying an electrolyte membrane to a water electrolysis device, from the perspective of suppressing the generation of hydrogen permeation, it is preferable to place the surface of the electrolyte membrane on the anode side where the platinum-containing component is more heavily present.

[0076] In this specification, "platinum-containing substances are more concentrated on one surface side of the electrolyte membrane" means that the concentration of platinum-containing substances in the region from one surface of the electrolyte membrane (hereinafter also referred to as "surface A") to a specified depth position (hereinafter also referred to as "depth position B") is higher than the concentration of platinum-containing substances in the region from surface C to depth position B.

[0077] In addition, "this aggregate is predominantly present on one surface side of the electrolyte membrane" means that the concentration of this aggregate in the region from surface A to depth B is higher than the concentration of cerium oxide in the region from surface C to depth B.

[0078] In addition, "the platinum-containing substances and the aggregate are predominantly present on one surface side of the electrolyte membrane" means that the concentration of platinum-containing substances in the region from surface A to depth B is higher than the concentration of platinum-containing substances in the region from surface C to depth B, and the concentration of the aggregate in the region from surface A to depth B is higher than the concentration of the aggregate in the region from surface C to depth B.

[0079] Here, one suitable way to ensure that the platinum-containing material is predominantly present on one surface side of the electrolyte membrane is as follows: depth position B, which is 50% of the membrane thickness from surface A. 50 The concentration ratio of platinum-containing substances in the region up to this point is from surface C to depth B. 50 The concentration of platinum-containing substances is high in the region to date.

[0080] use Figure 1 The example specifically illustrates the state where "the platinum-containing substance is predominantly present on one surface side of the electrolyte membrane". Figure 1 This is a cross-sectional schematic diagram of an electrolyte membrane used to illustrate the presence of platinum-containing substances.

[0081] exist Figure 1 In the electrolyte membrane 1, there are two surfaces: surface A1 as one surface and surface C1 as another surface. Depth position B1 represents the distance T traveled from surface A1 to surface C1. X The position of the length.

[0082] The shortest distance from surface A1 to surface C1 of electrolyte membrane 1, i.e., distance T1, is equivalent to the thickness of electrolyte membrane 1. X This is the length X% of the distance from T1. For example, the distance from T... X When the distance from T1 is 20%, the depth position B1 is equivalent to the following position: from the surface A1 of the electrolyte membrane 1, the position is equivalent to 20% of the membrane thickness of the electrolyte membrane 1 (distance from T1).

[0083] Region X represents the region from surface A1 to depth B1, and region Y represents the region from surface C1 to depth B1.

[0084] It should be noted that when the surface of the electrolyte membrane 1 is uneven, the above distances are measured based on the position where the electrolyte membrane 1 has the smallest thickness.

[0085] exist Figure 1 In this context, when the concentration of platinum-containing substances in region X is higher than that in region Y, it can be said that "platinum-containing substances are more concentrated on one surface side of the electrolyte membrane".

[0086] For the purposes of this disclosure, the platinum-containing material in the electrolyte membrane is preferably present from one surface of the electrolyte membrane to a position corresponding to 25%, particularly 20%, further 15%, and further 10% of the membrane thickness. Furthermore, the platinum-containing material in the electrolyte membrane is preferably present only at these thicknesses.

[0087] The location of platinum-containing substances and aggregates in the electrolyte membrane can be determined, for example, by using an energy-dispersive X-ray analyzer (product name "QUANTAX FlatQUAD", manufactured by Bruker) through elemental distribution.

[0088] Based on the obtained element distribution, the distance Tx mentioned above can be calculated.

[0089] As an example of a method to make the platinum-containing material predominate on one surface side of the electrolyte membrane, an example can be given by laminating a first electrolyte layer containing platinum-containing material and a second electrolyte layer having a lower concentration of platinum-containing material than the first electrolyte layer or containing no platinum-containing material to obtain an electrolyte membrane.

[0090] Other methods include: impregnating a solution containing platinum ions from a surface of an electrolyte membrane that does not contain platinum, so as to contain platinum between a surface of the electrolyte membrane and a predetermined depth position of the electrolyte membrane.

[0091] The thickness of the electrolyte membrane is preferably 30 μm or more, more preferably 60 μm or more, even more preferably 90 μm or more, and preferably 400 μm or less, more preferably 300 μm or less, even more preferably 200 μm or less, and particularly preferably 100 μm or less.

[0092] Furthermore, when aggregates in the electrolyte membrane act as shielding structures, forming areas where current flow is difficult and resistance may increase, the thickness of the electrolyte membrane is preferably 90 μm or more when the average particle size of the aggregates is 5 μm or more. When the average particle size of the aggregates is less than 5 μm, the thickness of the electrolyte membrane is preferably 60 μm or more. Additionally, the upper limits for each are preferably within the range of the aforementioned electrolyte membrane thicknesses.

[0093] It should be noted that when the electrolyte membrane has a multilayer structure, the thickness of the electrolyte membrane refers to the total thickness of all layers.

[0094] When the electrolyte membrane has a multilayer structure and has the first electrolyte layer and the second electrolyte layer described above, the ratio of the thickness of the first electrolyte layer to the thickness of the second electrolyte layer (thickness of the first electrolyte layer / thickness of the second electrolyte layer) is preferably 0.02 or more, more preferably 0.05 or more, even more preferably 0.12 or more, particularly preferably 0.19 or more, and preferably 0.80 or less, more preferably 0.50 or less, and even more preferably 0.30 or less.

[0095] The thickness of the electrolyte membrane was measured using a magnified image (e.g., 100x) of the cross-section of the electrolyte membrane taken with an optical microscope (product name "BX-51", manufactured by Olympus Corporation). It should be noted that if the surface of the electrolyte membrane is uneven, the thickness of the concave portions at 10 points and the thickness of the convex portions at 10 points are measured, and the arithmetic mean of the total thicknesses of these 20 points is taken as the thickness of the electrolyte membrane. Where the convex portions contain yarns constituting the fabric, the thickness of the convex portions is the value obtained by subtracting the thickness of the yarns present in the convex portions.

[0096] <Fluoropolymers (I)>

[0097] The electrolyte membrane contains a fluoropolymer (I).

[0098] Regarding the ion exchange capacity of the fluoropolymer (I), from the perspective of further reducing the electrolysis voltage when applied to a water electrolysis device, it is preferable to have 0.90 mE / g dry resin or more, more preferably greater than 1.10 mE / g dry resin, even more preferably 1.15 mE / g dry resin or more, particularly preferably 1.20 mE / g dry resin or more, and even more preferably 1.25 mE / g dry resin or more.

[0099] The ion exchange capacity of the fluoropolymer (I) is preferably 2.00 mE / g dry resin or less, more preferably 1.50 mE / g dry resin or less, further preferably 1.43 mE / g dry resin or less, and particularly preferably 1.35 mE / g dry resin or less, in terms of the strength of the membrane electrode assembly in water.

[0100] Fluoropolymer (I) can be used alone, or two or more can be layered or mixed together.

[0101] The electrolyte membrane may contain polymers other than fluoropolymer (I), but the polymers in the electrolyte membrane are preferably substantially composed of fluoropolymer (I). "Substantially composed of fluoropolymer (I)" means that the content of fluoropolymer (I) is 95% by mass or more relative to the total mass of the polymers in the electrolyte membrane. As an upper limit for the content of fluoropolymer (I), an example is 100% by mass relative to the total mass of the polymers in the electrolyte membrane.

[0102] As specific examples of polymers other than fluoropolymers (I), one or more polyazole compounds selected from the group consisting of polymers of heterocyclic compounds containing one or more nitrogen atoms in the ring and polymers of heterocyclic compounds containing one or more nitrogen atoms in the ring and containing oxygen atoms and / or sulfur atoms can be listed.

[0103] Specific examples of polyazole compounds include polyimidazolium compounds, polybenzimidazole compounds, polybenzimidazole compounds, polybenzobisimidazole compounds, polybenzoxazole compounds, polyoxazole compounds, polythiazole compounds, and polybenzothiazole compounds.

[0104] In addition, from the perspective of the oxidation resistance of the electrolyte membrane, polyphenylene sulfide resin and polyphenylene ether resin can be cited as specific examples of other polymers.

[0105] The fluoropolymer (I) has ion-exchange groups. Specific examples of ion-exchange groups include sulfonic acid type functional groups and carboxylic acid type functional groups. From the perspective of further reducing the electrolysis voltage when the electrolyte membrane is applied to a water electrolysis device, sulfonic acid type functional groups are preferred.

[0106] The following section will focus on fluoropolymers with sulfonic acid functional groups (hereinafter also referred to as "fluoropolymers (S)").

[0107] The fluoropolymer (S) preferably comprises units based on fluorinated olefins and units having sulfonic acid functional groups and fluorine atoms.

[0108] Examples of fluorinated olefins include 2- to 3-carbon fluorinated olefins having one or more fluorine atoms in their molecules. Specific examples of fluorinated olefins include tetrafluoroethylene (hereinafter also referred to as "TFE"), trifluorochloroethylene, vinylidene fluoride, vinyl fluoride, and hexafluoropropylene. Among these, TFE is preferred from the perspectives of monomer manufacturing cost, reactivity with other monomers, and the superior properties of the resulting fluorinated polymer (S).

[0109] Fluorinated olefins can be used alone or in combination of two or more.

[0110] As a unit having sulfonic acid functional groups and fluorine atoms, the unit shown in formula (1) is preferred.

[0111]

[0112] L is an optional perfluorocarbon group with an n+1 valence containing an ether-type oxygen atom.

[0113] The oxygen atom in an ether can be located at the end of a perfluorocarbon group or between carbon atoms.

[0114] The number of carbons in the n+1 valence perfluorocarbon group is preferably 1 or more, more preferably 2 or more, and further preferably 20 or less, more preferably 10 or less.

[0115] As L, preferably, it is a perfluoroaliphatic hydrocarbon group with an n+1 valence containing an ether oxygen atom; more preferably, it is a divalent perfluoroalkylene group with an ether oxygen atom as n=1, or a trivalent perfluoroaliphatic hydrocarbon group with an ether oxygen atom as n=2.

[0116] The aforementioned divalent perfluoroalkylene groups can be either straight-chain or branched.

[0117] M can be a hydrogen atom, an alkali metal, or a quaternary ammonium cation. Multiple M's can be the same or different.

[0118] n is 1 or 2.

[0119] As the unit shown in formula (1), the unit shown in formula (1-1), the unit shown in formula (1-2), the unit shown in formula (1-3), or the unit shown in formula (1-4) are preferred, and the unit shown in formula (1-1) is more preferred.

[0120]

[0121]

[0122]

[0123] R f1 The perfluoroalkylene group is optionally a perfluoroalkylene group containing an oxygen atom between carbon atoms. Preferably, the perfluoroalkylene group has 1 or more carbon atoms, more preferably 2 or more, and further preferably 20 or less, more preferably 10 or less.

[0124] R f2 It is a perfluoroalkylene group with a single bond or optionally containing an oxygen atom between carbon atoms. The number of carbon atoms in the perfluoroalkylene group is preferably 1 or more, more preferably 2 or more, and further preferably 20 or less, more preferably 10 or less.

[0125] R f3 It is a perfluoroalkylene group with a single bond or optionally containing an oxygen atom between carbon atoms. The number of carbon atoms in the perfluoroalkylene group is preferably 1 or more, more preferably 2 or more, and further preferably 20 or less, more preferably 10 or less.

[0126] r is 0 or 1.

[0127] m is 0 or 1.

[0128] M is as described above.

[0129] As for the unit shown in formula (1-1) and the unit shown in formula (1-2), the unit shown in formula (1-5) is more preferred.

[0130] Equation (1-5) -[CF2-CF(-(CF2)] x -(OCF2CFY) y -O-(CF2) z -SO3M)]-

[0131] x is 0 or 1, y is an integer from 0 to 2, z is an integer from 1 to 4, and Y is F or CF3. M is as described above.

[0132] As specific examples of the unit shown in equation (1-1), the following units can be listed. In the equation, w is an integer from 1 to 8, and x is an integer from 1 to 5. The definition of M in the equation is as described above.

[0133]

[0134] As specific examples of the unit shown in equation (1-2), the following units can be listed. In the equation, w is an integer from 1 to 8. The definition of M in the equation is as described above.

[0135]

[0136] As the unit shown in equation (1-3), the unit shown in equation (1-3-1) is preferred. The definition of M in the equation is as described above.

[0137]

[0138] R f4 It is a straight-chain perfluoroalkylene group with 1 to 6 carbon atoms, R f5 It is a straight-chain perfluoroalkylene group with 1 to 6 carbon atoms, consisting of a single bond or optionally containing oxygen atoms between carbon atoms. The definitions of r and M are as described above.

[0139] The following are specific examples of the unit shown in equation (1-3-1).

[0140]

[0141] As the unit shown in equation (1-4), the unit shown in equation (1-4-1) is preferred. R in the equation... f1 R f2 The definitions of M and M are as described above.

[0142]

[0143] The following are specific examples of the unit shown in equation (1-4-1).

[0144]

[0145] Units with sulfonic acid functional groups and fluorine atoms can be used alone or in combination of two or more.

[0146] Fluoropolymers (I) may contain units based on other monomers, in addition to units based on fluorinated olefins and units having sulfonic acid functional groups and fluorine atoms.

[0147] As a specific example of other monomers, CF2=CFR can be listed as follows: f6 (where R) f6 (perfluoroalkyl groups with 2 to 10 carbon atoms), CF2=CF-OR f7 (where R) f7 (A perfluoroalkyl group having 1 to 10 carbon atoms), and CF2=CFO(CF2). v CF = CF2 (where v is an integer from 1 to 3).

[0148] From the perspective of maintaining ion exchange performance, the content of units based on other monomers is preferably 30% by mass or less relative to all units in the fluoropolymer (I).

[0149] The content of fluoropolymer (I) is preferably 95 to 100% of the total mass of the electrolyte membrane.

[0150] Platinum-containing substances

[0151] The electrolyte membrane contains platinum.

[0152] Platinum-containing substances only need to contain platinum atoms. Specific examples of platinum-containing substances include platinum itself, platinum oxides, platinum-containing composite metal oxides, and platinum alloys.

[0153] As a specific example of a platinum-containing composite oxide, M can be cited. x Pt3O4 (M is at least one metal atom selected from the group consisting of Li, Na, Mg, Ca, Zn, Cd, Co, Ni, Mn, Cu, Ag, Bi and Ce, and x is greater than 0 and less than 1).

[0154] As a specific example of a platinum alloy, an alloy comprising at least one metal selected from the group consisting of transition metals and noble metals other than platinum, and platinum.

[0155] Specific examples of the shape of platinum-containing substances include granular and flake-like forms. When the platinum-containing substance is granular, it can be a core-shell type particle. Examples of core-shell type particles include those with a core of carbon or containing a metal other than platinum, and a shell containing platinum atoms.

[0156] When the platinum-containing material is in particulate form, the average particle size (D50) of the platinum-containing material is preferably 1 nm or more, more preferably 5 nm or more, even more preferably 10 nm or more, particularly preferably 100 nm or more, and preferably 10,000 nm or less, more preferably 5,000 nm or less, and even more preferably 3,000 nm or less.

[0157] The average particle size of the platinum-containing compound is the cumulative 50% diameter (D50) on a volume basis, obtained by dispersing the platinum-containing dispersion using a particle size distribution measuring device. Detailed measurement conditions are as follows: The dispersion containing the platinum-containing compound and the fluoropolymer was dispersed (using a bead mill), and the particle size distribution was measured using a laser diffraction particle size distribution measuring device (MicrotracBEL, MT3300EXII-SDC) to determine the cumulative 50% diameter on a volume basis for the platinum-containing compound. The arithmetic mean of the cumulative 50% diameters obtained from the three points was used as D50.

[0158] In addition, the particle size of 20 randomly selected platinum-containing particles can be determined from cross-sectional images of the electrolyte membrane taken using SEM (scanning electron microscope), SEM-EDX (energy-dispersive X-ray spectrometer), or TEM (transmission electron microscope), and the arithmetic mean of the cumulative 50% diameter on a volume basis can be set as D50.

[0159] per 1cm 2 The preferred mass of platinum-containing material in the electrolyte membrane is 0.010 mg / cm³. 2 The above, more preferably 0.013 mg / cm³ 2 The above is further preferred to be 0.015 mg / cm³. 2 In addition, the preferred concentration is 0.050 mg / cm³. 2 The following applies if the mass of the platinum-containing substance is 0.010 mg / cm³. 2 The above can further suppress the generation of hydrogen permeation. If the mass of the platinum-containing substance is 0.050 mg / cm³, 2 The following methods can further reduce the electrolysis voltage, enabling the provision of low-cost membrane electrode assemblies and water electrolysis devices.

[0160] When the electrolyte membrane has a multilayer structure, each 1 cm of at least one electrolyte layer (preferably the first electrolyte layer mentioned above) contained in the electrolyte membrane... 2 The preferred mass of platinum-containing material in the electrolyte layer is 0.010 mg / cm³. 2 The above, more preferably 0.013 mg / cm³ 2 The above is further preferred to be 0.015 mg / cm³. 2 In addition, the preferred concentration is 0.050 mg / cm³.2 The following applies if the mass of the platinum-containing substance is 0.013 mg / cm³. 2 The above can further suppress the generation of hydrogen permeation. If the mass of the platinum-containing substance is 0.050 mg / cm³, 2 The following methods can further reduce the electrolysis voltage, enabling the provision of low-cost membrane electrode assemblies and water electrolysis devices.

[0161] When the electrolyte membrane has a single-layer structure, the mass ratio of the platinum-containing material to the fluoropolymer (I) in the electrolyte membrane (mass of platinum-containing material / mass of fluoropolymer (I)) is preferably 0.0005 to 0.0040. A mass ratio of 0.0005 or higher can further suppress hydrogen permeation. A mass ratio of 0.0040 or lower can further reduce the electrolysis voltage, providing a low-cost membrane electrode assembly and water electrolysis device.

[0162] When the electrolyte membrane has a multilayer structure, the mass ratio (mass of platinum-containing material to mass of fluoropolymer (I)) in at least one electrolyte layer (preferably the first electrolyte layer described above) included in the electrolyte membrane is preferably 0.005 or more, more preferably 0.007 or more, even more preferably 0.014 or more, and preferably 0.024 or less. A mass ratio of 0.005 or more can further suppress hydrogen permeation. A mass ratio of 0.024 or less can further reduce the electrolysis voltage, providing a low-cost membrane electrode assembly and water electrolysis device.

[0163] Platinum-containing materials can be supported on a substrate. Specific examples of substrates include carbon black powder, graphitized carbon, carbon fibers, and carbon nanotubes.

[0164] When a platinum-containing substance is loaded onto a carrier, the loading amount of the platinum-containing substance relative to the total mass of the platinum-containing substance and the carrier is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, and preferably 50% by mass or less.

[0165] <This aggregate>

[0166] The electrolyte membrane contains this aggregate.

[0167] This aggregate is an aggregate containing cerium oxide particles with an average particle size of 0.1 to 10 μm. The aggregate containing cerium oxide particles preferably contains cerium oxide as a main component. The content of cerium oxide particles in this aggregate is preferably 80% by mass or more, more preferably 90% by mass, even more preferably 95% by mass or more, and may also be 100% by mass. That is, it can be an aggregate of cerium oxide particles.

[0168] Cerium oxide can be CeO2 (cerium oxide (IV)) or Ce2O3 (cerium oxide (III)), with CeO2 being preferred in terms of stability.

[0169] Cerium oxide can be doped with polyvalent metal ions such as zirconium and praseodymium.

[0170] The average particle size (D50) of this aggregate is 0.1 μm or more, more preferably 0.6 μm or more, even more preferably 1 μm or more, and particularly preferably greater than 3 μm. Furthermore, it is 10 μm or less, more preferably 8 μm or less, even more preferably 6 μm or less, and particularly preferably 5 μm or less. When the D50 of this aggregate is within the above range, it is possible to further suppress the rise in electrolysis voltage or the formation of pinholes after water electrolysis for a certain period of time.

[0171] In the method for determining the average particle size of this aggregate, the particle size of 20 randomly selected aggregates is measured in cross-sectional images of the electrolyte membrane taken using SEM, SEM-EDX, or TEM, and the arithmetic mean of the cumulative 50% diameter of the volume reference is set as D50.

[0172] As a method for adjusting the average particle size of this aggregate, one example that can be listed is adjusting the mixing conditions in the manufacturing method of the electrolyte membrane described later.

[0173] per 1cm 2 The preferred mass of this aggregate in the electrolyte membrane is 0.010 mg / cm³. 2 The above, more preferably 0.029 mg / cm³ 2 The above is further preferred to be 0.043 mg / cm³. 2 The above, especially preferred, is 0.088 mg / cm³. 2 The optimal value is 0.132 mg / cm³. 2 In addition, the preferred concentration is 1.000 mg / cm³. 2 The following is more preferably 0.500 mg / cm³ 2 The following is a further preferred value: 0.300 mg / cm³ 2 the following.

[0174] If the mass of this aggregate is 0.010 mg / cm³ 2 As a result, the electrolyte membrane turns whitish, making it easier to detect foreign matter present within it. Therefore, when applying the electrolyte membrane to a water electrolysis device, it can be used in a way that avoids the areas containing foreign matter, thus suppressing the formation of pinholes in the electrolyte membrane caused by foreign matter.

[0175] The mass of this aggregate is 0.300 mg / cm³. 2The following steps can further reduce the electrolysis voltage, enabling the provision of low-cost membrane electrode assemblies and water electrolysis devices.

[0176] <Weaving>

[0177] Electrolyte membranes consist of a fabric made of warp and weft yarns (hereinafter, warp and weft yarns are collectively referred to as "yarn").

[0178] Fabric weaving plays a role in improving the dimensional stability, strength, and operability of the electrolyte membrane.

[0179] From the perspective of further reducing the electrolysis voltage, the opening ratio of the fabric is preferably 50% or more, more preferably 55% or more, further preferably 60% or more, and particularly preferably 70% or more. In addition, from the perspective of having better strength of the membrane electrode assembly, it is preferably 90% or less, and more preferably 80% or less.

[0180] The opening ratio of the fabric is calculated using the following formula (ε) based on the average diameter R1 of the yarns constituting the fabric and the average spacing P1 between adjacent yarns in the fabric (hereinafter also referred to as "pitch P1").

[0181] Here, the average yarn diameter R1 refers to the arithmetic mean of the diameters of 10 randomly selected yarns from a magnified image (e.g., 100x) of the fabric surface obtained using a microscope. Additionally, the spacing P1 refers to the arithmetic mean of 10 randomly selected points at intervals from different locations within the magnified image (e.g., 100x) of the fabric surface obtained using a microscope.

[0182]

[0183] The denier number of the yarn constituting the fabric is 2 or more. From the perspective of better strength and dimensional stability of the membrane electrode assembly, it is preferably 10 or more, more preferably 15 or more. In addition, from the perspective of further reducing the electrolysis voltage, it is preferably 60 or less, more preferably 50 or less, and even more preferably 20 or less.

[0184] It should be noted that denier number is a value in grams (g / 9000m) representing the mass of 9000m yarn.

[0185] From the perspective of excellent strength and dimensional stability of the membrane electrode assembly, the density of the yarn constituting the fabric is preferably 50 threads / inch or more, more preferably 70 threads / inch or more, and even more preferably 90 threads / inch or more. In addition, from the perspective of being able to further reduce the electrolysis voltage, it is preferably 200 threads / inch or less, more preferably 150 threads / inch or less, and even more preferably 100 threads / inch or less.

[0186] The yarn constituting the fabric can be composed of either monofilament or multifilament, wherein the monofilament is composed of one filament and the multifilament is composed of two or more filaments, with monofilament being preferred.

[0187] From the perspective of superior yarn durability, the yarn constituting the fabric is preferably composed of materials selected from the group consisting of polytetrafluoroethylene (hereinafter also referred to as "PTFE"), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (hereinafter also referred to as "PFA"), polyether ether ketone (hereinafter also referred to as "PEEK"), and polyphenylene sulfide (hereinafter also referred to as "PPS").

[0188] From the perspective of superior yarn durability and strength, the yarn constituting the fabric is preferably composed of cut film yarn.

[0189] When the material constituting the fabric is PTFE, considering the optimal balance between the strength and operability of the electrolyte membrane, the fabric's weight per unit area is preferably 20 g / m². 2 The above, more preferably 30g / m 2 In addition, the preferred value is 40g / m³. 2 the following.

[0190] When the material constituting the fabric is PFA, considering the optimal balance between the strength and operability of the electrolyte membrane, the fabric's weight per unit area is preferably 10 g / m². 2 In addition, the preferred value is 30g / m³. 2 The following is more preferably 20g / m 2 the following.

[0191] When the material constituting the fabric is PEEK, considering the excellent balance between the strength and operability of the electrolyte membrane, the weight per unit area of ​​the fabric is preferably 5 g / m². 2 In addition, the preferred value is 40g / m³. 2 The following is more preferably 30g / m 2 the following.

[0192] When the material constituting the fabric is PPS, considering the optimal balance between the strength and operability of the electrolyte membrane, the fabric's weight per unit area is preferably 5 g / m². 2 In addition, the preferred value is 40g / m³. 2 The following is more preferably 30g / m 2 the following.

[0193] The content of woven fabric relative to the total mass of the electrolyte membrane is preferably 3% by mass or more, more preferably 5% by mass or more, and preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less.

[0194] <Methods for manufacturing electrolyte membranes>

[0195] As an example of a method for manufacturing an electrolyte membrane, the following methods can be listed.

[0196] First, a mixture of a polymer (hereinafter also referred to as "fluoropolymer (I')") containing a fluorinated monomer (hereinafter also referred to as "fluorinated monomer (I')"), a platinum-containing compound, and the present polymer is used to obtain a membrane P1 containing the fluoropolymer (I'), the platinum-containing compound, and the present polymer. Next, membrane P1, fabric, and membrane P1 are sequentially prepared and laminated using a laminating roller or vacuum laminating device to obtain a precursor membrane. Then, the groups in the precursor membrane that can be converted into ion exchange groups are converted into ion exchange groups to obtain an electrolyte membrane containing the fluoropolymer (I), the platinum-containing compound, the present polymer, and the fabric.

[0197] The above mixture is preferably pre-mixed using a mixer.

[0198] Examples of mixers include, for instance, twin-screw extruders. The mixing conditions can be appropriately varied depending on the average particle size of the desired aggregate. For example, when preparing aggregate A using a twin-screw extruder under mixing condition A, to prepare aggregate B with an average particle size smaller than aggregate A, if the mixing is carried out under mixing condition B, which reduces the discharge rate under mixing condition A and increases the screw speed, aggregate B can be obtained.

[0199] Other examples of methods for manufacturing electrolyte membranes include the following methods.

[0200] First, the groups in the fluoropolymer (I') that can be converted into ion exchange groups are converted into ion exchange groups to obtain the fluoropolymer (I). Next, a dispersion containing the fluoropolymer (I), the platinum-containing compound, and the polymer is impregnated into a fabric and then dried to obtain an electrolyte membrane containing the fluoropolymer (I), the platinum-containing compound, the polymer, and the fabric.

[0201] These methods yield a single-layer electrolyte membrane (equivalent to the first electrolyte layer mentioned above).

[0202] As an example of a method for manufacturing a multilayer electrolyte membrane, the following methods can be listed.

[0203] First, a membrane (precursor membrane) comprising a fluoropolymer (I') and a fabric is manufactured. Then, groups in the precursor membrane that can be converted into ion exchange groups are converted into ion exchange groups to obtain an electrolyte membrane A comprising the fluoropolymer (I) and the fabric. Next, an electrolyte membrane B is obtained by casting using a dispersion containing the fluoropolymer (I), a platinum-containing compound, and the polymer itself.

[0204] Next, electrolyte membrane A and electrolyte membrane B are prepared sequentially and stacked using a laminating roller or vacuum laminating device to obtain an electrolyte membrane comprising a fluoropolymer (I), a platinum-containing compound, the polymer itself, and a woven fabric. This yields a multilayer electrolyte membrane. In this multilayer electrolyte membrane, the platinum-containing compound and the polymer are predominantly present on one surface side of the electrolyte membrane.

[0205] Another example of a method for manufacturing a multilayer electrolyte membrane is as follows: a first electrolyte layer comprising a fluoropolymer (I), a platinum-containing compound, and the polymer itself is laminated with an electrolyte layer (equivalent to the second electrolyte layer described above) that does not contain platinum or has a platinum-containing compound concentration lower than that of the first electrolyte layer, followed by hot pressing. It should be noted that the fabric only needs to be included in at least one of the first and second electrolyte layers. Thus, a multilayer electrolyte membrane is obtained. In this multilayer electrolyte membrane, the platinum-containing compound is predominantly present on one surface side of the electrolyte membrane.

[0206] As a fluoropolymer (I'), a polymer having a fluorinated monomer (hereinafter also referred to as "fluorinated monomer (S')") that can be converted into a sulfonic acid functional group is preferred (hereinafter also referred to as "fluoropolymer (S')"). More preferably, a copolymer of a fluorinated olefin and a monomer having a group and a fluorine atom that can be converted into a sulfonic acid functional group is preferred.

[0207] The following is a detailed description of fluoropolymers (S').

[0208] Copolymerization of fluoropolymers (S') can be achieved using known methods such as solution polymerization, suspension polymerization, and emulsion polymerization.

[0209] As a fluorinated olefin, the substances previously exemplified can be listed. From the perspectives of monomer manufacturing cost, reactivity with other monomers, and the superior properties of the resulting fluorinated polymer (S), TFE is preferred.

[0210] Fluorinated olefins can be used alone or in combination of two or more.

[0211] As fluorine-containing monomers (S'), compounds that have one or more fluorine atoms in their molecules, have alkene double bonds, and have groups that can be converted into sulfonic acid functional groups can be listed.

[0212] As a fluorinated monomer (S'), the compound shown in formula (2) is preferred from the aspects of monomer manufacturing cost, reactivity with other monomers and excellent properties of the resulting fluorinated polymer (S).

[0213]

[0214] The definitions of L and n in equation (2) are as described above.

[0215] A represents a functional group capable of being converted into a sulfonic acid type. Preferably, the functional group capable of being converted into a sulfonic acid type through hydrolysis. Specific examples of functional groups capable of being converted into sulfonic acid type are -SO₂F, -SO₂Cl, and -SO₂Br. The n A's can be the same or different.

[0216] As the compound represented by formula (2), the compound represented by formula (2-1), the compound represented by formula (2-2), the compound represented by formula (2-3), or the compound represented by formula (2-4) are preferred.

[0217]

[0218]

[0219] R in the formula f1 R f2 The definitions of r and A are as described above.

[0220]

[0221] R in the formula f1 R f2 R f3 The definitions of r, m, and A are as described above.

[0222] As for the compounds shown in formula (2-1) and the compounds shown in formula (2-1), the compounds shown in formula (2-5) are preferred.

[0223]

[0224] The definitions of x, y, z, and Y in the formula are as described above.

[0225] As specific examples of the compounds shown in formula (2-1), the following compounds can be listed. In the formula, w is an integer from 1 to 8, and x is an integer from 1 to 5.

[0226]

[0227] As specific examples of the compounds shown in formula (2-2), the following compounds can be listed. In the formula, w is an integer from 1 to 8.

[0228]

[0229] As the compound represented by formula (2-3), the compound represented by formula (2-3-1) is preferred.

[0230]

[0231] R in the formula f4 R f5 The definitions of r and A are as described above.

[0232] The following are specific examples of compounds represented by formula (2-3-1).

[0233]

[0234] As the compound shown in formula (2-4), the compound shown in formula (2-4-1) is preferred.

[0235]

[0236] R in the formula f1 R f2 The definitions of A and A are as described above.

[0237] Specific examples of the compounds represented by formula (2-4-1) are listed below.

[0238]

[0239] Fluorinated monomers (s') can be used alone or in combination of two or more.

[0240] In the manufacture of fluoropolymers (S'), other monomers besides fluorinated olefins and fluorinated monomers (S') can also be used. Examples of other monomers previously exemplified can be listed.

[0241] The ion exchange capacity of fluoropolymer (I') can be adjusted by changing the content of groups in fluoropolymer (I') that can be converted into ion exchange groups.

[0242] Specific examples of methods for converting groups in the precursor membrane that can be converted into ion exchange groups include methods such as hydrolysis or acidification of the precursor membrane. Among these, contacting the precursor membrane with an alkaline aqueous solution is preferred.

[0243] Specific examples of methods for contacting a precursor membrane with an alkaline aqueous solution include immersing the precursor membrane in an alkaline aqueous solution and spraying an alkaline aqueous solution onto the surface of the precursor membrane.

[0244] The temperature of the alkaline aqueous solution is preferably 30°C or higher, more preferably 40°C or higher, and further preferably 100°C or lower. The contact time between the precursor membrane and the alkaline aqueous solution is preferably 3 minutes or more, more preferably 5 minutes or more, and further preferably 150 minutes or less, and more preferably 50 minutes or less.

[0245] The alkaline aqueous solution preferably contains an alkali metal hydroxide, a water-soluble organic solvent, and water.

[0246] Sodium hydroxide and potassium hydroxide are examples of alkali metal hydroxides.

[0247] In this specification, water-soluble organic solvent refers to an organic solvent that is readily soluble in water. Specifically, it is preferably an organic solvent with a solubility of 0.1 g or more in 1000 mL of water (20°C), more preferably an organic solvent with a solubility of 0.5 g or more. The water-soluble organic solvent preferably includes at least one selected from the group consisting of aprotic organic solvents, alcohols, and amino alcohols, more preferably including aprotic organic solvents.

[0248] Water-soluble organic solvents can be used alone or in combination of two or more.

[0249] Specific examples of aprotic organic solvents include dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, and N-ethyl-2-pyrrolidone, with dimethyl sulfoxide being preferred.

[0250] Specific examples of alcohols include methanol, ethanol, isopropanol, butanol, methoxyethoxyethanol, butoxyethanol, butylcarbitol, hexoxyethanol, octanol, 1-methoxy-2-propanol, and ethylene glycol.

[0251] Specific examples of amino alcohols include ethanolamine, N-methylethanolamine, N-ethylethanolamine, 1-amino-2-propanol, 1-amino-3-propanol, 2-aminoethoxyethanol, 2-aminothioethoxyethanol, and 2-amino-2-methyl-1-propanol.

[0252] The concentration of the alkali metal hydroxide in the alkaline aqueous solution is preferably 1% by mass or more, more preferably 3% by mass or more, and preferably 60% by mass or less, more preferably 55% by mass or less.

[0253] The content of water-soluble organic solvent in the alkaline aqueous solution is preferably 1% by mass or more, more preferably 3% by mass or more, and preferably 60% by mass or less, more preferably 55% by mass or less.

[0254] The concentration of water in the alkaline aqueous solution is preferably 39-80% by mass.

[0255] Alternatively, the alkaline aqueous solution can be removed after the precursor membrane has been in contact with it. One method for removing the alkaline aqueous solution is, for example, washing the precursor membrane with water after it has been in contact with the alkaline aqueous solution.

[0256] After the precursor membrane is contacted with an alkaline aqueous solution, the resulting membrane can be contacted with an acidic aqueous solution, thereby converting the ion exchange groups to the acidic form.

[0257] Specific examples of methods for contacting the precursor membrane with an acidic aqueous solution include immersing the precursor membrane in an acidic aqueous solution and spraying an acidic aqueous solution onto the surface of the precursor membrane.

[0258] The acidic aqueous solution preferably contains an acidic component and water.

[0259] Specific examples of acidic components include hydrochloric acid and sulfuric acid.

[0260] [Membrane electrode assembly]

[0261] The membrane electrode assembly disclosed herein only needs to include the electrolyte membrane described above.

[0262] The membrane electrode assembly preferably includes: the electrolyte membrane, a cathode catalyst layer disposed on one side of the electrolyte membrane, and an anode catalyst layer disposed on the other side of the electrolyte membrane.

[0263] Figure 2 This is a schematic cross-sectional view illustrating an example of the membrane electrode assembly of this disclosure. Figure 2 In one example, the membrane electrode assembly 20 includes: an anode 22 having a catalyst layer 26 and a gas diffusion layer 28; a cathode 24 having a catalyst layer 26 and a gas diffusion layer 28; and an electrolyte membrane 10 disposed between the anode 22 and the cathode 24 in contact with the catalyst layer 26.

[0264] exist Figure 2 The example shown illustrates a single-layer electrolyte membrane structure, but electrolyte membranes can also be multilayered. Specific examples and preferred configurations of multilayer electrolyte membranes are described above.

[0265] Figure 3 This is a schematic cross-sectional view illustrating an example of the membrane electrode assembly of this disclosure, and a diagram showing the case where the electrolyte membrane has a multilayer structure. Figure 3 The structure of the membrane electrode assembly 120, in addition to replacing Figure 2 In addition to the electrolyte membrane 100, the electrolyte membrane 10 is also present in the electrolyte membrane 100. Figure 2 The structure of the membrane electrode assembly 20 is the same. Figure 3 The electrolyte membrane 100 is arranged with a first electrolyte layer 100A and a second electrolyte layer 100B sequentially from the anode 22 side to the cathode 24 side.

[0266] The first electrolyte layer 100A comprises a fluoropolymer (I), a platinum-containing compound, and the polymer itself.

[0267] The second electrolyte layer 100B comprises a fluoropolymer (I) and this polymer. It should be noted that the concentration of platinum in the second electrolyte layer 100B is lower than that in the first electrolyte layer, or it contains no platinum.

[0268] At least one of the first electrolyte layer 100A and the second electrolyte layer 100B comprises a woven fabric.

[0269] exist Figure 3 The example shows a two-layer electrolyte membrane, but electrolyte membranes can also have three or more layers.

[0270] exist Figure 3 The example shown is an example in which only platinum is predominantly present on one surface side of the electrolyte membrane, but the electrolyte membrane included in the membrane electrode assembly of this disclosure may also be a mixture of platinum and this aggregate, both predominantly present on one surface side.

[0271] <Anode and Cathode>

[0272] Both the anode and cathode have catalyst layers. Figure 2 In the example, the anode 22 and the cathode 24 have a catalyst layer 26 and a gas diffusion layer 28, respectively.

[0273] As a specific example of a catalyst layer, a layer comprising a catalyst and a polymer having ion-exchange groups can be cited.

[0274] Specific examples of catalysts include supported catalysts on a carbon support containing platinum, platinum alloys, or platinum with a core-shell structure; iridium oxide catalysts; composite oxide catalysts containing iridium and other metal elements; alloys containing iridium oxide; and catalysts containing iridium oxide with a core-shell structure. Carbon black powder can be cited as a carbon support.

[0275] As a polymer having ion exchange groups, fluoropolymers having ion exchange groups can be listed, and fluoropolymer (I) described above can be used, for example.

[0276] per 1cm 2 The preferred mass of the catalyst metal in the catalyst layer is 0.05 mg / cm³. 2 The above, more preferably 0.2 mg / cm³ 2 In addition, 4 mg / cm³ is preferred. 2 The following is more preferably 2 mg / cm³ 2 The following is further preferred: 1 mg / cm³ 2 the following.

[0277] The mass ratio of the catalyst to the polymer with ion exchange groups in the catalyst layer (mass of catalyst / mass of polymer with ion exchange groups) is preferably 2 to 6.

[0278] The gas diffusion layer functions to rapidly diffuse gases generated from the catalyst layer outwards and also acts as a current collector. Specific examples of gas diffusion layers include carbon paper, carbon cloth, carbon felt, sintered titanium dioxide fibers, and sintered titanium dioxide particles. Since the anode side is at a high potential and carbon materials are oxidized when used, sintered titanium dioxide fibers or sintered titanium dioxide particles are preferred. The titanium dioxide sintered body can be coated with platinum or similar materials as needed.

[0279] The cathode gas diffusion layer can also be hydrophobically treated using PTFE or similar materials.

[0280] Figure 2 The membrane electrode assembly includes a gas diffusion layer 28, but the gas diffusion layer is an optional component and may not be included in the membrane electrode assembly.

[0281] The thickness of the anode and cathode is preferably 5 μm or more, and more preferably 100 μm or less, even more preferably 50 μm or less, further preferably 30 μm or less, and particularly preferably 15 μm or less.

[0282] The thicknesses of the anode and cathode were determined using images obtained by measuring a cross-section cut along the thickness direction of the membrane electrode assembly using a laser microscope, and were the arithmetic mean of any 20 points.

[0283] <Manufacturing Method of Membrane Electrode Assembly>

[0284] The method for manufacturing the membrane electrode assembly is to form a cathode catalyst layer on one side of the electrolyte membrane and an anode catalyst layer on the other side of the electrolyte membrane.

[0285] As an example of a method for manufacturing a membrane electrode assembly, the following method can be cited: using a laminate having an anode catalyst layer and a release substrate (e.g., ETFE (ethylene tetrafluoroethylene) sheet) and a laminate having a cathode catalyst layer and a release substrate (e.g., ETFE sheet), after bonding the catalyst layer to both sides of the electrolyte membrane, the release substrate is peeled off.

[0286] The aforementioned laminate may have a gas diffusion layer between the catalyst layer and the release substrate. In this case, the gas diffusion layer can be formed on the side of the catalyst layer opposite to the electrolyte membrane.

[0287] It should be noted that methods for manufacturing the catalyst layer include: applying a catalyst layer forming coating liquid to a specified location (e.g., the surface of a release substrate) and drying it as needed. The catalyst layer forming coating liquid is a liquid in which a polymer having ion exchange groups and a catalyst are dispersed in a dispersion medium.

[0288] <Applications>

[0289] The membrane electrode assembly disclosed herein is suitable for use in solid polymer water electrolysis devices.

[0290] [Water electrolysis apparatus and hydrogen production method]

[0291] The water electrolysis apparatus disclosed herein only needs to include the above-mentioned membrane electrode assembly.

[0292] The water electrolysis apparatus preferably includes: the membrane electrode assembly described above, a water supply unit that supplies water to the anode catalyst layer side, and a power supply unit that is electrically connected to both the anode catalyst layer side and the cathode catalyst layer side.

[0293] In the water electrolysis apparatus of this disclosure, when a DC voltage is applied by the power supply unit while water is supplied to the anode catalyst layer side by the water supply unit, water decomposes to produce oxygen and protons on the anode catalyst layer side. Additionally, on the cathode catalyst layer side, protons that have moved to the cathode catalyst layer side via the electrolyte membrane gain electrons to produce hydrogen.

[0294] In addition to the components described above, the water electrolysis apparatus disclosed herein may have the same configuration as known water electrolysis apparatuses (e.g., an oxygen recovery unit for recovering generated oxygen, and a hydrogen recovery unit for recovering generated hydrogen).

[0295] Furthermore, the hydrogen production method of this disclosure uses the water electrolysis apparatus of this disclosure to electrolyze water (electrolyte) to produce hydrogen. Since the hydrogen production method of this disclosure uses the water electrolysis apparatus of this disclosure, hydrogen can be produced efficiently.

[0296] Example

[0297] The present invention will now be described in detail with examples. Examples 1-7, 10 and 11 are embodiments, and examples 8 and 9 are comparative examples. However, the present invention is not limited to these examples.

[0298] [Ion exchange capacity of fluoropolymers]

[0299] The fluoropolymer was placed in a glove box purged with dry nitrogen for 24 hours, and its dry mass was determined. Subsequently, the fluoropolymer was immersed in a 2 mol / L sodium chloride aqueous solution at 60°C for 1 hour. After rinsing with ultrapure water, the fluoropolymer was removed, and the impregnated liquid was titrated with a 0.1 mol / L sodium hydroxide aqueous solution to determine the ion exchange capacity (mEq / g dry resin).

[0300] [Thickness of the electrolyte membrane]

[0301] The thickness of the electrolyte membrane was measured using a magnified image (50x objective) of the cross-section of the electrolyte membrane taken with a laser microscope (product name "VK-X1000", manufactured by KEYENCE) under conditions of temperature: 23°C and relative humidity: 50%RH.

[0302] [Average particle size of aggregates]

[0303] The average particle size of the aggregates containing cerium oxide particles is the arithmetic mean D50 of the cumulative 50% diameter of the volume-based aggregates obtained by measuring the particle size of any 20 aggregates in a cross-sectional image of the electrolyte membrane taken using SEM-EDX under the following conditions.

[0304] <Measurement Conditions>

[0305] Equipment: Hitachi High Technology Co., Ltd. SU6600 and Thermo Fisher Scientific Noran System 6

[0306] Accelerating voltage: 10kV

[0307] Working distance ≈ 15mm

[0308] Probe current: Medium

[0309] [Electrolysis voltage rises]

[0310] After heat-treating the membrane electrode assembly at 150°C for 15 minutes, it was placed in the water electrolysis evaluation fixture EH50-25 (manufactured by Greenlight Innovation).

[0311] Next, to ensure the solid polymer electrolyte membrane and the two electrode ionomers are fully hydrated, pure water with a conductivity of less than 1.0 μS / cm, a temperature of 80°C, and atmospheric pressure was supplied to the anode and cathode sides at a flow rate of 50 mL / min for 12 hours. Then, the cathode side was purged with nitrogen.

[0312] After nitrogen purging, pure water with a conductivity of less than 1.0 μS / cm, a temperature of 80°C, and atmospheric pressure is supplied to the anode side at a flow rate of 50 mL / min, so that the gas pressure generated on the cathode side is atmospheric pressure. Simultaneously, a PWR1600L DC power supply manufactured by Kikusui Electronics Co., Ltd. is used with a current density of 2 A / cm². 2 The system operates for 500 hours, and the voltage difference (voltage rise) between the start of operation and the end of 500 hours is used for evaluation. Evaluation A, B, C, or D is preferred.

[0313] A: When the voltage difference is less than 20mV

[0314] B: Cases where the voltage difference is greater than 20mV and less than 30mV

[0315] C: Cases where the voltage difference is greater than 30mV and less than 40mV

[0316] D: The voltage difference is greater than 40mV and less than 50mV.

[0317] E: Cases where the voltage difference is greater than 50mV

[0318] [Pinhole]

[0319] After heat-treating the membrane electrode assembly at 150°C for 15 minutes, it was placed in the water electrolysis evaluation fixture EH50-25 (manufactured by Greenlight Innovation).

[0320] Next, to ensure the solid polymer electrolyte membrane and the two electrode ionomers are fully hydrated, pure water with a conductivity of less than 1.0 μS / cm, a temperature of 80°C, and atmospheric pressure was supplied to the anode and cathode sides at a flow rate of 50 mL / min for 12 hours. Then, the cathode side was purged with nitrogen.

[0321] After nitrogen purging, pure water with a conductivity of less than 1.0 μS / cm, a temperature of 80°C, and atmospheric pressure is supplied to the anode side at a flow rate of 50 mL / min, so that the generated gas pressure on the cathode side is 0.9 MPa. Simultaneously, a PWR1600L DC power supply manufactured by Kikusui Electronics Co., Ltd. is used with a current density of 2 A / cm². 2 It can operate for 1000 hours.

[0322] After operation, the number of pinholes (openings) in the electrolyte membrane of the membrane electrode assembly is measured using a pinhole inspection device (product name "TRS-70", manufactured by SANKO ELECTRONIC LABORATORY CO., LTD.). Evaluation A or B is preferred.

[0323] A: There are no pinholes.

[0324] B: There are 1 to 2 pinholes.

[0325] C: There are more than 3 pinholes.

[0326] [Example 1]

[0327] First, CF2=CF2 is copolymerized with monomer (X) as shown in formula (X) below to obtain fluoropolymer (I'-1) (ion exchange capacity: 1.25 mEq / g dry resin). It should be noted that the ion exchange capacity in parentheses indicates the ion exchange capacity of the fluoropolymer obtained by hydrolyzing fluoropolymer (I'-1) according to the steps described later.

[0328]

[0329] Next, using a twin-screw extruder (manufactured by Nippon Steel), a fluoropolymer (I'-1), platinum black (Tanaka Precious Metals Co., Ltd. "TEC90300", platinum-containing compound), and cerium oxide (manufactured by Fujifilm and Kouichi Chemical Co., Ltd., primary particle size: less than 10 nm, CeO2) were blended to obtain a compound. It should be noted that the above blending conditions were adjusted by changing the discharge rate and screw speed to achieve the target average particle size of the aggregate containing cerium oxide particles. For example, if the discharge rate is reduced and the screw speed is increased, the average particle size of the resulting aggregate becomes smaller. The blended melt obtained in the heated mixing section of the twin-screw extruder was melted and extruded from a T-die, adhering the blended melt to a substrate made of linear low-density polyethylene (LLDPE) film (melting point: 110~120°C), resulting in a substrate Y1 with a film α1 (film thickness: 45 μm) formed on the substrate.

[0330] Additionally, using 18.6 denier PFA yarn as both warp and weft, and weaving at a PFA yarn density of 100 yarns / inch, fabric A1 was obtained. Fabric A1 has a basis weight of 16.3 g / m². 2 It should be noted that both the warp and weft yarns are composed of cut film filaments.

[0331] The substrate Y1 with a thin film, the fabric A1, and the substrate Y1 with a thin film are stacked in sequence. It should be noted that the substrate Y1 with a thin film is arranged such that the thin film α1 in the substrate Y1 is in contact with the fabric A1.

[0332] The overlapping components are subjected to a temperature of 160℃ and a surface pressure of 30MPa / m. 2 After being heated and pressed by a flatbed press for 10 minutes, the substrates on both sides are peeled off at a temperature of 50°C to obtain the precursor film.

[0333] In a solution of dimethyl sulfoxide / potassium hydroxide / water = 30.0 / 5.5 / 64.5 (mass ratio), the precursor membrane was immersed at 95°C for 30 minutes to hydrolyze the functional groups in the precursor membrane that could be converted to sulfonic acid groups, converting them to K-type sulfonic acid groups. The membrane was then washed with water. Next, the resulting membrane was immersed in 1M sulfuric acid to convert the terminal groups from K-type to H-type, and then dried to obtain electrolyte membrane 1 (90 μm thickness) of Example 1.

[0334] CF2=CF2 is copolymerized with the above monomer (X). The acidic fluoropolymer (ion exchange capacity: 1.10 mEq / g dry resin) prepared by hydrolysis and acid treatment is dispersed at a solid content concentration of 26.0% by mass in a solvent of water / ethanol = 40 / 60 (by mass) to obtain a dispersion (hereinafter also referred to as "dispersion Y").

[0335] Ethanol (18.06 g) and ZEORORA-H (manufactured by ZEON, Japan, 10.58 g) were added to the obtained dispersion Y (33.0 g), and mixed at 2200 rpm for 5 minutes using a THINKY Awatori Rentaro mixer. Ethanol (46.44 g) and water (75.75 g) were added to the mixed composition (54.06 g), and further added a solution containing 74.8% iridium with a specific surface area of ​​100 m² was added. 2 / g of iridium oxide catalyst (manufactured by Tanaka Precious Metals Co., Ltd.) (40.0g). The resulting mixture was treated with a planetary bead mill (300 rpm) for 90 minutes to obtain an anode catalyst ink with a solid content concentration of 22% by mass.

[0336] An anode catalyst ink was coated onto an ETFE sheet using a coater, resulting in an iridium concentration of 1.0 mg / cm². 2 The anode catalyst layer was dried at 80°C for 10 minutes and then further heat-treated at 150°C for 15 minutes to obtain the anode catalyst layer transfer body (decal).

[0337] Water (59.4 g) and ethanol (39.6 g) were added to 11 g of a supported catalyst (Tanaka Precious Metals Industry Co., Ltd. "TEC10E50E") with 46% platinum on carbon powder, and the mixture was pulverized using an ultrasonic homogenizer to obtain a catalyst dispersion.

[0338] A mixture (29.2 g) pre-mixed and kneaded from dispersion Y (20.1 g), ethanol (11 g), and ZEORORA-H (manufactured by ZEON, Japan) (6.3 g) was added to the catalyst dispersion. Then, water (3.66 g) and ethanol (7.63 g) were added to the resulting dispersion, and the mixture was stirred for 60 minutes using a coating adjuster to achieve a solids concentration of 10.0% by mass, thus obtaining the cathode catalyst ink.

[0339] Cathode catalyst ink was coated onto an ETFE sheet using a die-coating machine, dried at 80°C, and then heat-treated at 150°C for 15 minutes to obtain a platinum content of 0.4 mg / cm³. 2 The cathode catalyst layer transfer body.

[0340] The anode catalyst layer transfer body with the catalyst layer facing one side of the electrolyte membrane 1, and the cathode catalyst layer transfer body with the catalyst layer facing the other side of the electrolyte membrane 1, are heated and pressed for 10 minutes at a pressing temperature of 150℃ and a pressure of 3MPa to bond the anode catalyst layer, electrolyte membrane 1, and cathode catalyst layer. After the temperature is reduced to 70℃ and the pressure is released, the parts are removed. The ETFE sheets of the anode and cathode catalyst layer transfer bodies are then peeled off to obtain an electrode with an area of ​​16cm². 2 The resulting membrane electrode assembly was subjected to the evaluations described above. The results are shown in Table 1.

[0341] It should be noted that if foreign matter is identified when the electrolyte membrane 1 is visually inspected, the foreign matter is removed from the electrolyte membrane 1 before fabricating the membrane electrode assembly. The same applies to the following examples.

[0342] [Example 2~Example 11]

[0343] Change the conditions to those shown in Table 1 and adjust the mixing conditions as described below. Otherwise, prepare each membrane electrode assembly using the same steps as in Example 1.

[0344] For example, compared to Example 1, the mixing conditions in Example 2 increased the discharge rate and decreased the screw speed. Compared to Example 2, the mixing conditions in Example 3 further increased the discharge rate and decreased the screw speed. Compared to Example 1, the mixing conditions in Example 8 decreased the discharge rate and increased the screw speed. Compared to Example 5, the mixing conditions in Example 9 increased the discharge rate and decreased the screw speed. Regarding the other examples, the mixing conditions were changed in the same way as described above to make the aggregates containing cerium oxide particles have the average particle size listed in Table 1.

[0345] In the table, IEC (meq / g) represents the ion exchange capacity (milliequivalents / g dry resin) of the fluoropolymer (I).

[0346] Mass of platinum-containing substances (mg / cm³) 2 ) indicates per 1cm 2 The mass of platinum-containing material in the electrolyte membrane.

[0347] The average particle size (μm) of the aggregates represents the average particle size of the aggregates containing cerium oxide particles.

[0348] Mass of aggregate (mg / cm³) 2) indicates per 1cm 2 The mass of the aggregate containing cerium oxide particles in the electrolyte membrane.

[0349] Using the membrane electrode assembly obtained in each example, the above-described evaluations of electrolysis voltage rise and pinholes were performed. The results are shown in Table 1.

[0350] It should be noted that in the above evaluation of pinholes, for the example with evaluation result A (i.e., the example in which no pinholes were generated), if the evaluation is carried out by changing the generation gas pressure on the cathode side to 2MPa, it can also be confirmed in this evaluation that no pinholes were generated.

[0351] [Table 1]

[0352]

[0353] As shown in Table 1, it is confirmed that the electrolyte membrane of this disclosure can suppress the rise of the electrolysis voltage after water electrolysis for a certain period of time and is not prone to pinholes.

[0354] Furthermore, the entire contents of the specification, claims, drawings, and abstract of Japanese Patent Application No. 2023-221212, filed on December 27, 2023, are incorporated herein as a disclosure of the specification of this invention.

[0355] Explanation of reference numerals in the attached figures

[0356] 1, 10, 100 Electrolyte membrane

[0357] 20,120 membrane electrode assembly

[0358] 22 Anode

[0359] 24 Cathode

[0360] 26 Catalyst Layer

[0361] 28 Gas diffusion layer

[0362] 100A First Electrolyte Layer

[0363] 100B Second Electrolyte Layer

[0364] A1, C1 surfaces

[0365] B1 Depth Position

[0366] T1,T X distance

[0367] X,Y area

Claims

1. A solid polymeric electrolyte membrane comprising: a fluoropolymer having ion-exchange groups, a platinum-containing compound, an aggregate containing cerium oxide particles, and a fabric. The average particle size of the aggregates is 0.1–10 μm.

2. The solid polymer electrolyte membrane according to claim 1, wherein, The average particle size of the aggregates is greater than 3 μm.

3. The solid polymer electrolyte membrane according to claim 1, wherein, The ion exchange capacity of the fluoropolymer is 0.90~2.00 milliequivalents / gram of dry resin.

4. The solid polymer electrolyte membrane according to claim 1, wherein, per 1cm 2 The mass of the aggregate in the solid polymer electrolyte membrane is 0.010 mg / cm³. 2 above.

5. The solid polymer electrolyte membrane according to claim 1, wherein, The platinum-containing material is predominantly present on one surface side of the solid polymer electrolyte membrane.

6. The solid polymer electrolyte membrane according to claim 1, wherein, The platinum-containing compound is loaded onto a carrier.

7. The solid polymer electrolyte membrane according to claim 1, wherein, The fluorinated polymer has sulfonic acid functional groups as its ion exchange groups.

8. The solid polymer electrolyte membrane according to claim 1, wherein, The fluoropolymer comprises the unit shown in formula (1-1), In equation (1-1), R f1 M is a perfluoroalkylene group that optionally contains oxygen atoms between carbon atoms, and M is a hydrogen atom, an alkali metal, or a quaternary ammonium cation.

9. The solid polymer electrolyte membrane according to claim 1, wherein, The fabric is made of a material selected from the group consisting of polytetrafluoroethylene, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, polyether ether ketone and polyphenylene sulfide.

10. A membrane electrode assembly comprising: The solid polymer electrolyte membrane according to any one of claims 1 to 9 The cathode catalyst layer disposed on one side of the solid polymer electrolyte membrane, and An anode catalyst layer is disposed on the other side of the solid polymer electrolyte membrane.

11. A water electrolysis device, comprising: The membrane electrode assembly as described in claim 10; A power supply unit, which is connected to the cathode catalyst layer side and the anode catalyst layer side in the membrane electrode assembly; and The water supply unit supplies water to the anode catalyst layer side.

12. A method for producing hydrogen, comprising electrolyzing water using the water electrolysis apparatus of claim 11 to produce hydrogen.

13. A method for manufacturing a membrane electrode assembly, the membrane electrode assembly comprising: a solid polymer electrolyte membrane according to any one of claims 1 to 9, a cathode catalyst layer, and an anode catalyst layer. In the manufacturing method, the cathode catalyst layer is formed on one side of the solid polymer electrolyte membrane, and the anode catalyst layer is formed on the other side of the solid polymer electrolyte membrane.

Citation Information

Patent Citations

  • Membrane electrode assembly, solid polymer electrolyte membrane, waer electrolysis system and electrolytic hydrogenation system

    WO2022050363A1